1999
DOI: 10.1210/endo.140.1.6455
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Thioredoxin, a Redox-Active Protein, by Ovarian Steroid Hormones during Growth and Differentiation of Endometrial Stromal Cells in Vitro**This work was supported by a Grant-in-Aid for Scientific Research, Japan.

Abstract: Human thioredoxin (hTrx) is a cellular redox-active protein that catalyzes dithiol/disulfide exchange reactions, thus controlling multiple biological functions, including cell growth-promoting activity. Here we show that the expression of hTrx protein and messenger RNA was up-regulated by incubation with 17beta-estradiol (E2) in primary culture of stromal cells isolated from human endometrium. Maximal enhancement of hTrx protein and messenger RNA was observed after 6-12 h of incubation with 10-100 nM E2, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Thioredoxin (Q99757) is one of the major proteins regulating intracellular redox metabolism and it is activated in response to oxidative stress. Studies have shown that the expression of thioredoxin mRNA can be induced by estrogen [29]. The direct evidence of the increased expression of thioredoxin upon estrogen exposure has never been reported.…”
Section: Proteins With Changes In Expressionmentioning
confidence: 99%
“…Thioredoxin (Q99757) is one of the major proteins regulating intracellular redox metabolism and it is activated in response to oxidative stress. Studies have shown that the expression of thioredoxin mRNA can be induced by estrogen [29]. The direct evidence of the increased expression of thioredoxin upon estrogen exposure has never been reported.…”
Section: Proteins With Changes In Expressionmentioning
confidence: 99%